FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN PROPERTY TAHUN 2014 – 2016 DI BURSA EFEK INDONESIA - Asia, Nur (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to analyze the Factors Affecting Stock Return on Property Sector Companies period 2014 – 2016 on Indonesia Stock Exchange. The variables used to meas Price Earning Ratio (PER), current ratio (CR), Total Asset Turnover (TAT), Net Profit Margin (NPM), and debt to equity ratio (DER) .The Factors Affecting Stock Return on Property Sector Companies is the current ratio (CR), return on equity (ROE), and debt to equity ratio (DER). While the variables used to measure the company's share price is the closing price. The population of this research is the property sector company, listed on the Stock Exchange Period 2014-2016 with a total of 47 companies. The sampling method used was purposive sampling with a sample of 29 companies. This study uses multiple regression analysis with significance level of 5% alpha. The results of this study show that TAT has positive and significant effect on stock return, variable PER and NPM has positive but not significant effect on stock return and varIable CR and DER has signifcant negative effect on stock return in property company in Indonesian Stock Exchange.